Le début du ive s. av. J.-C. dans l’espace culturel sénonais : les habitats de Bois d’Echalas à Ville-Saint-Jacques et de Beauchamp à Varennes-sur-Seine (Seine-et-Marne) dans le contexte de l’interfluve Seine-Yonne - Jean-Marc Séguier; Ginette Auxiette; Benoît Clavel; Olivier Maury; Sylvie Rimbault (Revue Archéologique du Centre de la France)
The study of two settlements of the beginning of the 4th century BC near the confluence of the Seine and the Yonne enables us to define the movable culture of this part of the Paris basin during La Tène B1a, notably because of the association of an important series of local and imported ceramics and significant metal articles. The analysis of the structures of conservation and of furniture lead to the establishment of a hierachy of settlements. That of Ville-Saint-Jacques, Bois d’Echalas, occupied a prominent place in the social system set up in the region in question, whereas that of Varennes-sur-Seine, Beauchamp, proved to be of a lower level. Beyond the comparison between the two sites, what is presented is a socio-economic lecture on territorial organisation.